Minutes of the Oxford paving commissioners, 1771-1801 - Graham, Malcolm 1948- (Boydell & Brewer Ltd, 2023)
Oxford Town and Gown came together in 1771 as Paving Commissioners, the city's principal local government body. Within thirty years this collaboration transformed Oxford from a medieval to a modern city. Eighteenth century Oxford was a place of great contrast with the architectural splendour of its university and college buildings set among narrow streets and timber-framed houses. Ancient gates and market stalls obstructed traffic and rubbish piled up in unpaved streets. Neither Town nor Gown could satisfy the growing appetite for urban improvement so they came together after centuries of rivalry in 1771 in a remarkable collaboration to sponsor a Local Act establishing Oxford Paving Commissioners as the city's principal local government body. The commissioners included the vice-chancellor and the mayor, heads of colleges, professors, councillors and local businessmen. A minority of these commissioners used the authority's extensive powers to rebuild Magdalen Bridge and reshape its approaches, abolish street markets, pull down old buildings, and pave, light and cleanse the streets. Some critics regretted these changes, others wanted more, but all could agree that, within thirty years, Oxford had been transformed